2015
DOI: 10.1093/ndt/gfv375
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological relevance of pretransplant anti-angiotensin II type 1 receptor antibodies in renal transplantation

Abstract: Pretransplant AT1R-Abs is an independent risk factor for AR, especially acute cellular rejection, and is possibly associated with the risk of antibody-mediated injury. Pretransplant assessment of AT1R-Abs may be useful for stratifying immunologic risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
8
42
0
Order By: Relevance
“…Pretransplant sensitization against AT1R, in patients without DSA, has been associated a higher prevalence of intimal arteritis and was demonstrated to be an independent predictor of vascular or ABMR rejection . Overall, our results confirm that the pretransplant presence of AT1R‐abs with or without concomitant DSA is an independent predictor of acute rejection, as previously reported …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Pretransplant sensitization against AT1R, in patients without DSA, has been associated a higher prevalence of intimal arteritis and was demonstrated to be an independent predictor of vascular or ABMR rejection . Overall, our results confirm that the pretransplant presence of AT1R‐abs with or without concomitant DSA is an independent predictor of acute rejection, as previously reported …”
Section: Discussionsupporting
confidence: 89%
“…Studied cohort median value was 8.2 UI/mL (interquartile range: 6.4–10.0). A value of 10 UI/mL was considered to be the cut‐off for positivity, given that it was the 3rd quartile value in our cohort and considering its association with clinical outcomes as previously published …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding duplicates, the titles and abstracts from the remaining 99 records were screened. Of these, 21 articles were selected for full text review, and nine articles were ultimately retained in our meta-analysis (see Figure 1) [12,13,14,15,16,21,22,23,24]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, AR after kidney allograft transplantation frequently progresses to persistent chronic rejection and dysfunction of kidney allograft, and ultimately results in kidney graft failure [11], indicating that AT1R-Abs may also influence the long-term outcomes of kidney allograft transplantation. Currently, several studies have shown that AT1R-Abs might be associated with an increased risk of acute rejection and kidney graft failure [12,13,14]; however, the results are inconsistent and inconclusive [15,16]. …”
Section: Introductionmentioning
confidence: 99%